Analisis Determinasi Minat Belanja Online: Bukti Empiris tentang Kemudahan Penggunaan dan Promosi Harga: Analysis of Determinants of Online Shopping Interest: Empirical Evidence on Ease of Use and Price Promotion - Rayhan Kurniawan; Amanda Fitriyanti; Radhelia Najla Syukuraeni; Farid Nasywan Zuhdi; Fany Fany; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
The development of online shopping platforms has driven changes in consumer behavior in meeting daily needs. This study aims to analyze the determinants of online shopping interest : empirical evidence on ease of use and price promotions. This study uses a quantitative approach with a survey method. The research instrument, a questionnaire consisting of 20 statement items, has been tested for validity and all items are declared valid with a calculated r value greater than r table (0.186). Data were collected from 112 respondents who are active online shopping users with diverse characteristics based on gender, age, and employment status. Data analysis was conducted descriptively to describe the tendency of respondents' perceptions regarding ease of use, clarity of information, and transaction convenience. The results show that the majority of respondents have a positive perception of online shopping platforms and show a high intention to continue using and recommending them to others. These findings indicate that ease of use and user experience are important factors in increasing consumer loyalty to online shopping platforms.